Evaluation of the oncolytic activity of Newcastle disease virus (rLS1) in human prostate and renal carcinoma cell lines - Guerrero-Fonseca, Gloria (2025)
Introduction. Oncolytic virotherapy has emerged as a novel method for treating cancer. The newcastle disease virus (ndv) exhibits oncolytic potential and selectively replicates in tumor cells. Human prostate and renal cancer are the leading causes of death worldwide. Objective. To evaluate the oncolytic activity of the rLS1 viral construct on prostate carcinoma (DU-145) and renal cancer (786-O) cell lines, as well as its selective replication in both tumor lines and the non-tumoral madin-darby canine kidney (MDCK) cell line. Methods. The oncolytic effectiveness was determined by reducing cell viability and apoptosis using the (3-[4,5-dimethylthiazol-2-yl]-5-[3-carboxymethoxyphenyl]-2-[4-sulfophenyl]-2h-tetrazolium) MTS colorimetric assay and by labeling with annexin v/anxa5-pe/sytox blue dead cell, respectively. The viral replicative selectivity in cells was evaluated by crystal violet staining. Results. The MTS assay determined that rls1 significantly reduced viability (p < 0,001) in both tumor cell lines without causing a significant reduction in the viability of MDCK cells compared to uninfected cells. A significant increase (p < 0,001) in the percentage of apoptotic cells was observed in 786-O and DU-145 cells infected with rLS1 compared to uninfected cells. Conclusion. The results indicate that rLS1 demonstrated selective oncolytic potential in human prostate and renal cancer cells, suggesting its potential as an antitumoral agent.